1981
DOI: 10.1121/1.2019074
|View full text |Cite
|
Sign up to set email alerts
|

Attraction of gray whales, Eschrichtius robustus, to underwater outboard engine noise in Laguna San Ignacio, Baja California Sur, Mexico

Abstract: off-shore drilling, human movements, unidentified machinery, tugs, and other marine service craft. The recordings, made in winter, spring, and fall, were obtained from under the ice, or from leads, polynyas, or open water at distances from a.few meters to about 185 km from the source. Estimated overall source levels varied from 40 to over 200 dB re 1 /xPa at 1 m, in the effective bandwidths. Principal acoustic energy occurred in bands falling between 10 Hz and 13 kHz. Among the lowest levels encountered were t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
1

Year Published

1984
1984
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 0 publications
0
1
1
Order By: Relevance
“…These whales voluntarily approach stationary vessels and remain nearby for hours, resulting in elevated risks to participants due to the close proximity of large animals, and to the focal whales due to boat strikes and/or entanglement with ropes used by swimmers (Mangott et al 2011). These results bear similarities to the “boat‐positive” behavior of gray whales ( Eschrichtius robustus ) in Mexico (Dalheim et al 1981), but are starkly different from other descriptions of large whale reactions to vessel traffic. The Scientific Committee of the International Whaling Commission noted that the impact of tourism activity may vary by species or site, and each situation should be evaluated on its individual merits (IWC 2000).…”
contrasting
confidence: 57%
“…These whales voluntarily approach stationary vessels and remain nearby for hours, resulting in elevated risks to participants due to the close proximity of large animals, and to the focal whales due to boat strikes and/or entanglement with ropes used by swimmers (Mangott et al 2011). These results bear similarities to the “boat‐positive” behavior of gray whales ( Eschrichtius robustus ) in Mexico (Dalheim et al 1981), but are starkly different from other descriptions of large whale reactions to vessel traffic. The Scientific Committee of the International Whaling Commission noted that the impact of tourism activity may vary by species or site, and each situation should be evaluated on its individual merits (IWC 2000).…”
contrasting
confidence: 57%
“…Since acoustical communication is almost certainly necessary to maintain contact between gray whale mothers and their newborn calves (Dahlheim, 1987), human-induced underwater noise may interfere with this and other important social behaviours. Dahlheim (1983) and Dahlheim et al (1984) reported that gray whales in Laguna San Ignacio (evidently necessarily) became more vocal when exposed to man-made noises, and Jones et al (1994) and Dahlheim et al (1995) found that most gray whales, especially cow/calf pairs, abandoned Laguna San Ignacio for a year in response to a month of underwater playback experiments of noises from outboard motors of boats, industrial activities and other sources, including killer whale vocalisations. As mentioned previously, the only records of gray whales inside Bahía de Yavaros were at a time when killer whales were sighted in the area outside this coastal lagoon.…”
Section: Discussionmentioning
confidence: 99%